Directing the architecture of surface-clean Cu₂O for CO electroreduction - Liu, Jiawei (2023)
Tailoring the morphology of nanocrystals is a promising way to enhance their catalytic performance. In most previous shape-controlled synthesis strategies, surfactants are inevitable due to their capability to stabilize different facets. However, the adsorbed surfactants block the intrinsic active sites of the nanocrystals, reducing their catalytic performance. For now, strategies to control the morphology without surfactants are still limited but necessary. Herein, a facile surfactant-free synthesis method is developed to regulate the morphology of Cu2O nanocrystals (e.g., solid nanocube, concave nanocube, cubic framework, branching nanocube, branching concave nanocube, and branching cubic framework) to enhance the electrocatalytic performance for the conversion of CO to n-propanol. Specifically, the Cu2O branching cubic framework (BCF-Cu2O), which is difficult to fabricate using previous surfactant-free methods, is fabricated by combining the concentration depletion effect and the oxidation etching process. More significantly, the BCF-Cu2O-derived catalyst (BCF) presents the highest n-propanol current density (−0.85 mA cm–2) at −0.45 V versus the reversible hydrogen electrode (VRHE), which is fivefold higher than that of the surfactant-coated Cu2O nanocube-derived catalyst (SFC, −0.17 mA cm–2). In terms of the n-propanol Faradaic efficiency in CO electroreduction, that of the BCF exhibits a 41% increase at −0.45 VRHE as compared with SFC. The high catalytic activity of the BCF that results from the clean surface and the coexistence of Cu(100) and Cu(110) in the lattice is well-supported by density functional theory calculations. Thus, this work presents an important paradigm for the facile fabrication of surface-clean nanocrystals with an enhanced application performance.